Recognition of sexual pleasure as a human right : a critical analysis of the Maputo Protocol - Ngwena, Charles (University of Pretoria, 2024)
Mini Dissertation (MPhil (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2024.